(untitled) (Asian Journal of Social Science Studies, 2022)
By using lacquer painting creation with realistic themes as an example, this essay will examine the primary issues with lacquer painting creation with realistic themes in the context of the modern period.It will summarize the key pathways and construction expansion choices for lacquer painting creation with realistic themes by analyzing the creative issues and traits of lacquer painting with realistic themes, and it will provide the future path perspective that may be supported.Modern lacquer paintings with realistic topics suffer from a loss of pictoriality, a weakening of pictoriality, and a lack of aesthetic merit. Lack of creative integrity and originality; little aesthetic effect; lack of a modern viewpoint or historical significance. It is clear that there is a “tendency to profit,” and commercialization results in repetition and homogenization. A few representative lacquer paintings and artworks have been examined by the author.By emphasizing the incorporation of styles from other forms of painting and increasing the lacquer painting‟s creative expressive language, the author offers answers.The development of lacquer paintings with realistic subjects in the context of the new period is suggested as well as workable solutions.